Mixed Metals Sandwich‐Type Polyoxotungstogermanate with Morpholine Ligand: Synthesis, Crystal Structure, and Magnetic Properties. Issue 12 (12th August 2014) - Jiang, Ning; Li, Bo; Xu, Lin; Wang, Yu‐Chao; Li, Jian‐Mei
Abstract The polyoxotungstate (C4H10ON)9H3[Mn2Na2(C4H10ON)2(GeW9O34)2]·9H2O (1) was synthesized in aqueous solution and characterized by single‐crystal and powder X‐ray diffraction, IR spectroscopy, TGA, and variable temperature susceptibility measurements. The polyoxoanion framework of 1 is built on the lacunary Keggin‐type polyanion [GeW9O34]10–. The central core shows [Mn2Na2(μ4‐O)2(μ3‐O)6(μ2‐O)8(C4H10ON)2] where the morpholine molecule is bound to the Na+ ion. The polyanions of 1 are further bridged into a one‐dimensional (1D) chain by the hydrogen bonding interactions. The magnetic investigations demonstrate the presence of antiferromagnetic exchange interactions for 1.